2002
DOI: 10.1021/la026041l
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Layered Docosyltrimethyl- and Docosyltriethylammonium Silicates Derived from Kanemite into Precursors for Ordered Mesoporous Silicas

Abstract: The transformation of layered silicate-surfactant materials derived from a layered polysilicate kanemite into precursors for ordered mesoporous silicas was investigated. When kanemite was allowed to react with docosyltrimethylammonium (C22TMA) and docosyltriethylammonium (C22TEA) surfactants, layered C22-TMA-and C22TEA-silicate materials were formed. The 29 Si MAS NMR spectra of the layered intermediates clearly indicated that fragmented silicate sheets were present in the silicate-surfactant materials. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…It is worthwhile to note that the reported catalytic results and the conclusions concerning the distribution of Al in FSM-16 solids have important implications for understanding the mechanism of FSM-16 formation. In particular, they represent an indirect evidence for the postulated occurrence of fragmentation of kanemite layers [10][11][12][13], since only then a preferential accumulation of Al at the inner pore walls of directly aluminated solids is conceivable. This issue will be discussed in detail in our forthcoming paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile to note that the reported catalytic results and the conclusions concerning the distribution of Al in FSM-16 solids have important implications for understanding the mechanism of FSM-16 formation. In particular, they represent an indirect evidence for the postulated occurrence of fragmentation of kanemite layers [10][11][12][13], since only then a preferential accumulation of Al at the inner pore walls of directly aluminated solids is conceivable. This issue will be discussed in detail in our forthcoming paper.…”
Section: Resultsmentioning
confidence: 99%
“…The present work reports the results of catalytic oxidation of cyclohexene with iodosylbenzene over metalloporphyrin supported on aluminated mesoporous silicas of FSM-16 type, which are materials obtained from synthetic layered mineral kanemite [9]. It has been demonstrated that the kanemitederived materials are formed via mechanism essentially different from that of MCM-41, despite the use in both cases of cationic surfactants as structure directing agents [10][11][12][13]. It has been proposed that, after intercalation of the surfactant cations between the silicate layers, a transformation occurs to a layered mesophase containing fragmented silicate sheets, which is the actual precursor of the FSM-16 structure.…”
Section: Introductionmentioning
confidence: 96%
“…57 Moreover, lamellar and FSM-16 materials have also been synthesized using docosyltrimethylammonium-kanemite and docosyltriethylammonium-kanemite complexes, respectively. 96,97 On the other hand, mesoporous silica with square channels (KSW-2) 98,99 has been obtained by adjusting the pH of the layered CTMAkanemite complex to a pH of 4.0-6.0 with 1 M acetic acid. The formation mechanism of KSW-2 is different from that found in FSM-16, and proceeds mainly through the bending of individual silicate sheets and subsequent intralayer and interlayer condensation.…”
Section: Transformation Of Layered Silicates Into Zeolitesmentioning
confidence: 99%
“…On the basis of these previous studies, we tried to prepare FSM-16 using C 22 TMA surfactant, which tends to be assembled as a lamellar phase. [71] Both the presence of a layered C 22 TMA-silicate intermediate composed of fragmented silicate sheets and the subsequent transformation into a 2D hexagonal phase during acid treatment were ascertained. We elucidated experimentally that FSM-16-type mesoporous silica is formed via layered intermediates composed of fragmented silicate sheets and C n TMA cations.…”
Section: On the Difference Between Fsm-16 And Mcm-41mentioning
confidence: 99%
“…[69,70] The formation mechanisms of the ordered mesoporous silica derived from kanemite have been proven only recently on the basis of experimental results. [71] An ordered mesoporous silica with an unusual mesostructure (KSW-2), which is not defined by using the geometrical packing of hexadecyltrimethylammonium (C 16 TMA) ions, was also discovered in one of the kanemite-surfactant systems. [72] The structural units of kanemite are retained in the silicate framework.…”
mentioning
confidence: 99%